An engineering approach to dry friction behaviour of numerous engineering plastics with respect to the mechanical properties - G. Kalacska (eXPRESS Polymer Letters, 2013)
Twenty-one different commercial-grade engineering polymers, including virgin and composite types, were selected for testing, based on mechanical engineering practices. Three groups were formed according to typical applications: 1) Sliding machine element materials; 2) Mechanically load-carrying machine element materials that are often subjected to friction and wear effects; and 3) Additional two amorphous materials used as chemically resistant materials that have rare sliding load properties. The friction running-in state was tested using a dynamic pin-on-plate test rig. During steady-state friction tests, two pv regimes (0.8 and 2 MPa"ms–1) were analysed by a pin-on-disc test system. Based on the measured forces on ground structural steel, surface friction coefficients were calculated and analysed with respect to the mechanical effects of friction. The friction results were evaluated by the measured mechanical properties: yield stress, Shore D hardness, Young’s modulus and elongation at the break. The three material groups exhibited different trends in friction with respect to changing mechanical properties. Linear (with varying positive and negative slopes), logarithmic and exponential relationships were observed, and occasionally there were no effects observed. At steady-state friction, the elongation at the break had less effect on the friction coefficients. The dynamic sliding model, which correlates better to real machine element applications, showed that increasing hardness and yield stress decreases friction. During steady-state friction, an increase in pv regime often changed the sign of the linear relationship between the material property and the friction, which agrees with the frictional theory of polymer/steel sliding pairs.